Community dental clinics in British Columbia, Canada: examining the potential as health equity interventions. (28th November 2014) - Wallace, Bruce B.; MacEntee, Michael I.; Pauly, Bernadette
Abstract Community dental clinics (CDCs) have emerged to provide oral healthcare for those with low incomes. In British Columbia, the establishment of community clinics has been quite rapid in recent years. However, the expansion has occurred with very little assessment of their impact or effectiveness. While oral health inequities are well recognised, there is limited documentation on healthcare interventions to reduce oral health inequities. This study examines CDCs as health equity interventions from the perspectives of individuals establishing and operating the clinics. The study included interviews with 17 participants – 4 dentists, 6 dental hygienists and 7 clinic managers – from 10 clinics operating in British Columbia, Canada in 2008–2009. A thematic analysis of the interview transcripts, explored through a health equity framework, found many ways in which the CDCs exemplify health equity interventions. Although their design and mandates are varied, they potentially enable access to dental treatment, but without necessarily ensuring sustainable outcomes. Moreover, the scalability of CDCs is questionable because frequently they are limited to emergency care and are less responsive to the gradients of needs for populations facing multiple barriers to care. Many of them operate on a charitable base with input from volunteer dentists; however, this foundation probably eases the pressure on dentists and dental hygienists rather than offering a safety net to underserved populations.